Esthesioneuroblastoma and Olfactory Preservation: Is it Reasonable to Attempt Smell Preservation? - Gompel, Jamie J. Van; Janus, Jeffrey R.; Hughes, Joshua D.; Stokken, Janalee K.; Moore, Eric J.; Ryan, Tarek; Price, Daniel L.; Link, Michael J. (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objective Olfactory preservation after resection of esthesioneuroblastoma (ENB) has been reported, however, the ability to predict tumor involvement of the olfactory system is critical to this surgical strategy. This study aims to answer the question: Can a surgeon predict, based on preoperative imaging, whether there is unilateral involvement of the olfactory system allowing for safe attempt of olfactory preservation?Methods This is a retrospective review of post-resection ENB meeting inclusion criteria of having bilateral olfactory tracts and bulbs submitted at the time of primary resection for pathologic margins. Five board-certified skull base surgeons blinded to the pathology individually reviewed the preoperative MRI scans to predict degree of tumor involvement.Results Olfactory bulb involvement occurred in both bulbs in 35% of cases and unilateral in 39% of cases, and there was no involvement in 26% of cases sampled. When comparing physician prediction of involved tracts or bulbs, involvement was appropriate or over-called (i.e., called positive when pathology was in fact negative) in 96% of cases.Conclusion This study demonstrates unilateral or no pathologic olfactory involvement of the olfactory system in 65% of cases. Our ability to predict this involvement, which may allow for a management strategy that attempts to preserve olfactory function, was accurate at 96%. Therefore, interpretation of imaging and proceeding with smell preservation in ENB appears reasonable in this cohort.Level of Evidence: Level 2b.
Keywords: esthesioneuroblastoma; olfactory neuroblastoma; outcome; olfactory nerve; surgical treatment